2020
DOI: 10.48550/arxiv.2007.08713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

True-Time-Delay Arrays for Fast Beam Training in Wideband Millimeter-Wave Systems

Abstract: The best beam steering directions are estimated through beam training, which is one of the most important and challenging tasks in millimeter-wave and sub-terahertz communications. Novel array architectures and signal processing techniques are required to avoid prohibitive beam training overhead associated with large antenna arrays and narrow beams. In this work, we leverage recent developments in true-time-delay (TTD) arrays with large delay-bandwidth products to accelerate beam training using frequency-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Past work on TTD array [1]- [3], [6] have shown that this architecture creates a prism-type response by radiating all the frequencies in all the directions in a linear fashion (Fig. 3(c)) by using a fixed set of delays at each antenna given by τ n = n B , for bandwidth B.…”
Section: A Primer On Phased Arrays and True-time Delay Arraysmentioning
confidence: 99%
“…Past work on TTD array [1]- [3], [6] have shown that this architecture creates a prism-type response by radiating all the frequencies in all the directions in a linear fashion (Fig. 3(c)) by using a fixed set of delays at each antenna given by τ n = n B , for bandwidth B.…”
Section: A Primer On Phased Arrays and True-time Delay Arraysmentioning
confidence: 99%